PROFIL PENDERITA TUMOR OVARIUM GERMINAL DI RSUD ARIFIN ACHMAD PROVINSI RIAU PERIODE JANUARI 2008 – DESEMBER 2012 - Pratama, Gerry; Sofian, Amru; Chandra, Fifia (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2014)
Ovarian tumour is one of neoplasma that can be found on female genitalia system, which is formed by benign wether malignant ovarium cells and can be grouped by its origin such as epithelial, germinal, and stroma ovarian tumour. Age, parity, cancer in family history, menarche history and application of hormonal contraception can be risk factors to germinal ovarian tumour to occurs.This is a descriptive and retrospective study, conducted to discover profile of germinal ovarian tumour patients in General Hospital Arifin Achmad Riau Province. From General Hospital Arifin Achmad’s medical records on January 2008-December 2012, 78 cases of germinal ovarian tumour have been found, with the age of majority was in the age 23-32 years old (36,11%), most parity was multiparity (40,27%) and most commonly histopatological type was mature teratoma (76,39%). Cancer in family history can be found in 29 patients (40,27%) which about 17 patients with mature teratoma (23,61%), followed by 8 patients with dysgerminoma (11,11%) and 4 patients with immature teratoma (5,55%). Based on menarche history, distribution profile by the age of majority was 10-13 years old (58,3%). About 62,5% patients didn’t use hormonal contraception. Most commonly CA 125 tests with positive results were 18 examinations (25%) wich can be found mature teratoma on 12 examinations (16,67%) followed by dysgerminoma on 4 examinations (5,56%) and immature teratoma on 2 examinations (2,77%). CEA tests showed positive results for about 14 examinations (19,44%), where mature teratoma can be found on 8 examinations (11,11%), followed by dysgerminoma on 4 examinations (5,56%) and immature teratoma on 2 examinations (2,77%). Salphingoophorectomy were the most common therapy that have been chosen (54,17%).Keywords: ovarian tumour, germinal ovarian tumour, risk factors